Extraction of Parasitic Elements of a Printed Circuit Board applied to a GaN Half-Bridge - Kohlhepp, Benedikt; Faber, Samuel; Kaiser, Jeremias; Kübrich, Daniel; Dürbaum, Thomas (PCIM Europe Conference Proceedings, 2022)
Modern semiconductors like GaN enable high efficient converter designs and fast switching transitions. In order to achieve full performance of these components in terms of switching behavior, parasitic inductances of the switching cell must be accurately known and minimized, since they have a significant influence on the switching transitions. Due to optimized device packages and PCB layouts, these are in the range of nH or even pH, which make accurate measurements very difficult or impossible. Thus, field simulations are the only way to obtain self and mutual inductances of the commutation loop as well as of the gate loops. This paper shows that commutation loop inductances below 1 nH are possible. The common source inductance, which represents the common conductive path as well as mutual couplings, is in the range of pH for a GaN-half-bridge.
CRIS-Team Scopus Importer:2022-06-10